(untitled) (World Bulletin of Public Health, 2024)
Congenital myopia (myopia) is caused by impaired development of the eyeball during intrauterine development. It is often caused by prematurity, hypoxia, and various diseases of the mother during the first three months of pregnancy. Normally, children are born hypermetropic, i.e. farsighted. The child’s eyeball is shortened, and light rays passing through the refractive media of the eye are focused not on the retina, but behind it. In small children, farsightedness of a weak degree is a natural age norm and with time (by the age of six or seven) passes, because as the child grows, the eyeball enlarges and the optical focus moves to the retina. In congenital myopia, the child is born with an elongated eyeball, which means that light rays do not reach the retina. This is very dangerous, as this condition interferes with the correct formation of the visual analyser and, as a consequence, the overall development of the baby